#### Answer

$\dfrac {1}{2}$

#### Work Step by Step

$e^{4x-1}=\left( e^{2}\right) ^{x}\Rightarrow e^{4x-1}=e^{2x}\Rightarrow 4x-1=2x\Rightarrow 2x=1\Rightarrow x=\dfrac {1}{2}$

Published by
Pearson

ISBN 10:
013421742X

ISBN 13:
978-0-13421-742-0

$\dfrac {1}{2}$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.